State of Cd₁₋xZnxTe and Cd₁₋xMnxTe surface depending on treatment type - Dremlyuzhenko, S.G.; Zakharuk, Z.I.; Rarenko, I.M.; Srtebegev, V.M.; Voloshchuk, A.G.; Yurijchuk, I.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
The morphology and composition of Cd₁₋xZnxTe and Cd₁₋xMnxTe solid solutions surfaces after different types of surface treatment were investigated. Chemical etching of the surfaces and polishing by diamond pastes cause change of surface stoichiometry and ontamination
of surface layer by carbon and etchant components. Potentiometer studies were carried out to study the processes that take place on the interface "semiconductor-electrolyte". A prediction of phase composition of oxide films on Cd₁₋xZnxTe and Cd₁₋xMnxTe surfaces was made and a mechanism of their dissolution was determined. It was found that chemicomechanical polishing by alkaline colloidal silica compositions is an optimal surface treatment procedure. Chemico-mechanical polishing with this mixture gives a uniform surface without essential change of surface stoichiometry and fouling of the surface layer by etchant components.